An array of simple, fast, and safe approaches to visualizing fine cellular structures in free-hand sections of stem, leaf, and fruit using optical microscopy - Bondada, Bhaskar R (Current Botany, 2012)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">A wide array of free-hand-sectioning-based optical microscopy techniques that are simple, safe, and inexpensive, yet allows quick and easy identification of specific cell types and cellular components with unprecedented resolution are presented using leaf (Saintpaulia ionantha and Schefflera actinophylla), stem (Vitis vinifera and V. labruscana), and fruit (Vitis vinifera) tissues. The objective of this study was to generate contrast and capture high quality cellular images of various plant organs either via infusing basic fuchsin, a xylemic dye into organs or using naturally pigmented organs by employing the classic technique of free-hand sectioning. Also, images were obtained via post-staining free-hand sections of organs without any dye infusion. Leaves injected with dye revealed its strikingly regular and hierarchical reticulate venation structure. The free-hand sections of healthy and water-stressed leaf petioles, and stems and pedicels prepared from organs either infused with basic fuchsin or post-stained with safranin displayed exceptional cellular details. These included the xylic and phloic transport systems positioned around the central parenchymatous pith, their tissue pattern in each system, and occlusion of xylem vessels by the parenchymatous tissues (tylosis). The free-hand sections of fruit revealed fine details of its translucent mesocarp embedded with vasculature of varied architecture, and seed morphology. Free-hand sections of naturally chromated petioles illustrated its internal structure pertaining to anthocyanin accumulating cells and crystals in superb details, and particularly, the most visually spectacular images of trichomes. Since observations of internal structures of plants constitute the foundations of plant biology, the microscopy techniques illustrated in this study can be of great interest and benefit to both addressing fundamental questions in plant biology and curiosity-driven research.